STRUKTUR DAN KOMPOSISI VEGETASI HUTAN SEMUSIM HABITAT CURIK BALI (LEUCOPSAR ROTHSCHILDI STRESEMANN, 1912) DI KAWASAN LABUAN LALANG, TAMAN NASIONAL BALI BARAT - Roemantyo, Roemantyo (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTVegetation structure and composition of Bali Starling (Leucopsar rothschildi Stresemann,1912) Habitat at Labuan Lalang monsoon forest, Bali Barat National Park. Research wasconducted in Labuan Lalang monsoon forest, Bali Barat National Park in May 2010 to identifytheir vegetation structure and composition of plant species communities in this area. Thisinformation was important as basic data for developing model for habitat reconstruction ofendemic Bali starling birds (Leucopsar rothschildi Stresemann 1912). Several ecologicalparameters information such as name species, frequency, density and abundance of individualspecies were collected for qualitative an quantitative analyses.The result showed that 93 species belonging 84 genera and 37 families were found in this area.Some plant species were recorded as endangered such as Strycnos lingustrina, Helicteresixora, Protium javanicum, Rauvolfia serpentina, Zanthoxylum rhetza, Ziziphus rotundifolia,Ceriops tagal, Flacourtia indica, and Santalum album. The important species that composedin this forest were dominated by Grewia ericocarpa , Schoutennia ovata (Tiliaceae) andfollowed by Vitex trifoliata and Abutilon indicum. The species diversity and evenness indexof Shannon-Wiener indicated that species diversity in this forest were not too high and thepopulations on unstable condition. Principal Coordinat Analyses (PCO) on the tree height andaltitude data of every tress showed that tree species associated to Bali starling were found onthe 10 ? 25 m tree hiehgt community and occupied in the area of 40 ? 60 m asl. The problems andreal condition of the area as the habitat of Bali starling were discussed in this paper.Key words: vegetation, species diversity, Bali starling, Bali Barat National Park